Islamic Religious Education Teacher Professionalism in Building a Religious School Environment: A Literature Review of Role Modelling, Religious Habituation, and School Culture - Aimi (CV. Jalan Cendikia, 2026)
This article aims to analyze the professionalism of Islamic Religious Education teachers in building a religious school environment through a narrative literature review. The study is grounded in the important role of Islamic Religious Education teachers in integrating Islamic values into learning, role modelling, religious habituation, school culture, and collaboration with families. The data were obtained from scholarly literature related to Islamic Religious Education teacher professionalism, religious character education, teacher role modelling, religious habituation, religious school culture, and students’ character formation. The data were analyzed using qualitative content analysis and thematic synthesis. The findings show that the professionalism of Islamic Religious Education teachers is not limited to mastery of subject matter and pedagogical competence, but also includes moral integrity, spiritual maturity, role modelling, and the ability to develop an Islamic-value-based school culture. Teacher role modelling strengthens value internalization, religious habituation shapes repeated religious behavior, while school culture institutionalizes Islamic values in rules, interactions, and daily practices. This study confirms that a religious school environment is formed through the consistency of Islamic Religious Education teachers in presenting Islamic values pedagogically, morally, spiritually, inclusively, and dialogically.